1997
DOI: 10.1021/jm970099t
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Mediated Generation of the Neurotoxin 6-Hydroxydopamine Quinone by Reaction of Fatty Acid Hydroperoxides with Dopamine:  A Possible Contributory Mechanism for Neuronal Degeneration in Parkinson's Disease

Abstract: Exposure of dopamine to an excess of linoleic acid 13-hydroperoxide (13-hydroperoxyoctadecadienoic acid) in the presence of ferrous ions in Tris buffer, pH 7.4, resulted in a relatively fast, oxygen-independent reaction exhibiting first-order kinetics with respect to both catecholamine and metal concentrations. Product analysis in the early stages revealed the presence of significant amounts of the quinone of the neurotoxin 6-hydroxydopamine, together with some aminochrome and ill-defined melanin-like material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 22 publications
1
95
0
3
Order By: Relevance
“…7). Iron is abundant in the SN and can react in a Fenton-type reaction with DA and hydrogen peroxide (produced extensively by monoamine oxidase during DA turnover) to produce 6-OHDA (43), which, in turn, can increase iron release from ferritin (35). This suggests that 6-OHDA may play an important role in perpetuating this damaging endogenous cycle.…”
mentioning
confidence: 99%
“…7). Iron is abundant in the SN and can react in a Fenton-type reaction with DA and hydrogen peroxide (produced extensively by monoamine oxidase during DA turnover) to produce 6-OHDA (43), which, in turn, can increase iron release from ferritin (35). This suggests that 6-OHDA may play an important role in perpetuating this damaging endogenous cycle.…”
mentioning
confidence: 99%
“…Both enzymatic and non-enzymatic catabolisms of dopamine are accelerated by the presence of redox active elements such as iron, zinc, or manganese [17] . The SNpc contains much higher concentration of iron than other brain regions, and it has been suggested that the increase in iron levels may catalyze the conversion of H 2 O 2 , which could be produced during the breakdown of dopamine, to highly reactive hydroxyl radicals, and thus resulted in increased oxidative damage in this region [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presence of 6-OHDA was seen to associate with increased activity of monoamine oxidase (MAO)-B, the enzyme bound to the outer mitochondrial membrane for catalyzing the oxidation of monoamines. It was shown that 6-OHDA is readily auto-oxidized and oxidatively deaminated by MAO, yielding hydrogen peroxide (H 2 O 2 ), which, in turn, generates hydroxyl radicals (-OH), the most reactive of these being ROS [17,18], as well as producing corresponding p-quinone. 6-OHDA quinine triggers a cascade of oxidative reactions, resulting in the formation of an insoluble polymeric pigment that is related to neuromelanin [19].…”
Section: Experimental Toxins Support a Role For Mitochondrial Patholomentioning
confidence: 99%